Розвиток професійних навчальних закладів мелітопольського округу в 1923–1930 рр. - Александров, Д.В.; Александрова, Г.І.; Шкода, Н.А. (Культура народов Причерноморья, 2014)
В научной статье исследуется проблема развития профессиональных учебных учреждений
Мелитопольского округа в 1923 – 1930 гг., их материальная база, источники финансирования,
специализация. Анализируются особенности функционирования профшкол сельскохозяйственной,
индустриально-технической, медицинской и социально-экономической направленности в регионе.
Дается характеристика реорганизационных изменений в данных учреждениях Мелитопольского региона
во второй половине 20-х гг. The article examines the problem of development of technical and vocational educational
establishments in Melitopol district from 1923 to 1930. Authors analyze the financial base, sourcing,
specialization of full-time technical and vocational training educational institutions in Melitopol district.
It was found out, that during 1920th the network of vocational training facilities and public technical education
establishments in Melitopol district was increased. This group of educational establishments was presented by
technical secondary schools, labour colonies, courses and factory training. They can be classified as
agricultural vocational schools, industrial technical colleges, medical and socio-economic institutions.
The most numerous were agricultural vocational schools. It is explained by mainly agrarian specialization of
Melitopol district. The most known schools of this type are Novomikolaivska agricultural school, and
Bogdanivska vocational school. Industrial technical colleges of the Melitopol district carried out the preparation
of turners from metal and tree treatment, of locksmiths and mechanics. There were also numerous schools of
socio-economic specialization: co-operative schools, accounting courses, tailoring courses in this period.
Financial possibilities of local authorities were limited and thus determined the pitiful financial state of most
educational establishments of this type. In the second half of the 20-ies in vocational education Melitopol district
reorganization changes occur mainly within the existing educational institutions. У науковій статті досліджується проблема розвитку професійних учбових установ
Мелітопольського округу в 1923 – 1930 рр., їх матеріальну базу, джерела фінансування, спеціалізація.
Аналізуються особливості функціонування профшкіл сільськогосподарської, індустріально-технічної,
медичної і соціально-економічної спрямованості в регіоні. Дається характеристика реорганізаційних
змін в цих установах Мелітопольського регіону у другій половині 20-х р.